1999
DOI: 10.1017/s0022377898007417
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic and ponderomotive self-focusing at laser–plasma interaction

Abstract: The nonlinear plasma dielectric function due to relativistic electron motion is derived. From this, one can obtain the nonlinear refractive index of the plasma and estimate the importance of relativistic self-focusing in comparison with ponderomotive non-relativistic self-focusing at very high laser intensities. When the laser intensity is very high, ponderomotive self-focusing will be dominant. However, at some point, when the oscillating velocity of the plasma electrons becomes very large, relativistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 3 publications
0
24
0
Order By: Relevance
“…For the 0.21 TW laser power, the Z = 13 copper ions are expected to have a maximum energy of 22.6 MeV (Hora et al 2002b) in agreement with the numerous measurements of several groups in the past. The final result for the maximum ion energy ε trans after relativistic self-focusing (Hora 1975;Jones et al 1982;Häuser et al 1992;Osman et al 1999;, fitting with all the long years of observations (Haseroth et al 1996) with laser pulses longer than 100 ps, was found to be dependent on the laser power P , the ion charge Z and the focused beam Number of (integrated signal) emitted fast ions and thermal ions from a perpendicular irradiated copper target at neodymium glass irradiation for 1.2 ps pulses depending on the laser pulse energy focused to a 30 wavelength diameter beam at the target surface with suppression of a prepulse by 10 8 for a time less then 100 ps before the main pulse arrived. During the last 100 ps the contrast ratio was about 10 4 (Badziak et al 1999(Badziak et al , 2003Hora, Badziak et al 2002a). diameter δ in multiples of the laser vacuum wave length (larger than 0.6) as in the following relation:…”
Section: Experiments Confirming the Skin Layer Interactionmentioning
confidence: 99%
“…For the 0.21 TW laser power, the Z = 13 copper ions are expected to have a maximum energy of 22.6 MeV (Hora et al 2002b) in agreement with the numerous measurements of several groups in the past. The final result for the maximum ion energy ε trans after relativistic self-focusing (Hora 1975;Jones et al 1982;Häuser et al 1992;Osman et al 1999;, fitting with all the long years of observations (Haseroth et al 1996) with laser pulses longer than 100 ps, was found to be dependent on the laser power P , the ion charge Z and the focused beam Number of (integrated signal) emitted fast ions and thermal ions from a perpendicular irradiated copper target at neodymium glass irradiation for 1.2 ps pulses depending on the laser pulse energy focused to a 30 wavelength diameter beam at the target surface with suppression of a prepulse by 10 8 for a time less then 100 ps before the main pulse arrived. During the last 100 ps the contrast ratio was about 10 4 (Badziak et al 1999(Badziak et al , 2003Hora, Badziak et al 2002a). diameter δ in multiples of the laser vacuum wave length (larger than 0.6) as in the following relation:…”
Section: Experiments Confirming the Skin Layer Interactionmentioning
confidence: 99%
“…In such a case the nonlinearity in the dielectric function occurs is caused by the electron mass variation due to large laser irradiance and the change in electron density as a consequence of the ponderomotive force. Very few studies on self focusing [35,36] and cross focusing [37] of the laser beams have been made, incorporating the combined effect of relativistic and ponderomotive nonlinearities. Further the effect of an ultra intense laser pulse on the propagation of an electron plasma wave has been analyzed by Kumar et al [38] in the relativistic-ponderomotive regime.…”
Section: Introductionmentioning
confidence: 99%
“…However, in our parameter range with lower laser intensity, the relativistic contribution is entirely negligible. 21 The related periodic focusing and defocusing may be typical for an integrable nonlinear paraxial equation 22 with an appropriate initial condition. For I 0 = 150I cr [see point B in Fig.…”
Section: Numerical Simulations and Nonlinear Dynamicsmentioning
confidence: 99%